A Bayesian Network Meta-Analysis for Identifying the Optimal Taxane-Based Chemotherapy Regimens for Treating Gastric Cancer - Zhang, Dan; Wu, Jia-Rui; Duan, Xiao-Jiao; Wang, Kai-Huan; Zhao, Yi; Ni, Meng-Wei; Liu, Shu-Yu; Zhang, Xiao-Meng; Zhang, Bing (Frontiers in Pharmacology, 2019)
Background: Several taxane-based chemotherapy regimens are effective in the treatment of gastric cancer; nevertheless, their comparative efficacy and safety remain disputed. This network meta-analysis (NMA) was designed to compare the efficacy and safety of different taxane-based chemotherapy regimens against gastric cancer. Methods: A comprehensive search was conducted to identify all relevant randomized controlled trials (RCTs) in multiple electronic databases. A Bayesian NMA was performed to combine the direct and indirect evidence and estimate the comparative efficacy and safety of different taxane-based chemotherapy regimens simultaneously by utilizing WinBUGS 1.4.3 and Stata 13.1 software. The efficacy outcomes included overall survival rate (OS), progression-free survival (PFS), and overall response rate (ORR), and the safety outcomes were adverse reactions (ADRs), namely, neutropenia, leucopenia, vomiting, and fatigue. Results: A total of 37 RCTs were identified involving 7,178 patients with gastric cancer, and 10 taxane-based chemotherapy regimens (RT, T, TC, TCF, TF, TO, TOF, mTCF, mTF, and mTOF) were collected in gastric cancer therapy. According to the results of cluster analysis, compared with other taxane-based chemotherapy regimens, the regimens of TOF, mTCF, and TF were associated with the most favorable clinical efficacy in improving OS, PFS, and ORR. On the other hand, the regimens of T and mTF had the potential to be the most tolerable and acceptable therapeutic alternative in terms of ADRs. Conclusions: The current NMA provides the evidence that the combination of taxanes (paclitaxel or docetaxel) and fluorouracil is associated with the most preferable and beneficial option for patients with gastric cancer, although additional results from multicenter trials and high-quality studies will be pivotal for supporting our findings.